Literature Review: Teknik Relaksasi untuk Penerimaan Diri Pasien Kanker Payudara - Ni Made Merlin; Anggorowati Anggorowati; Chandra Bagus Ropyanto; Antonius Rino Vanchapo (Jurnal Kesehatan, 2019)
Breast cancer patients experience low self-acceptance and some of the experiencing psychological problems but not a lot of research to increasing self-acceptance. Additional intervention is needed to improve the effectiveness to increase self-acceptance. Technique relaxation is especially related because easy and quick to learn, it involves no risk, does not need use or purchased equipment and can be used on its own and immediately to tiredness and ill patients. This paper offers a literature review assessing the implications of previous studies order to create evidence-based decisions about the possibility to use of relaxation techniques with adult breast cancer patient for low self-acceptance. The Science Direct, EBSCOhost, Pubmed, DOAJ, Google Scholar database were searched in 2017 in orders to replied two questions: are relaxation technique effective to increase self-acceptance in breast cancer patients, and implications the previous investigation to future research concerning increase self-acceptance in breast cancer patients? Four articles included in the literature review. The relaxation technique for breast cancer patients with low self-acceptance is statically significant, and good evidence-based to practice. Some use of relaxation techniques in this study needs clarification as to whether it can be used directly or need to learn. Procedures in the collection of data in the articles also need to be assessed. In this literature review explain 4 relaxation technique to use for increasing self-acceptance in breast cancer, there are self-forgiveness, meditation, tai-chi, reflection, prayer, mindfulness. This literature review can be used as the basis for the decision to use relaxation techniques for increasing self-acceptance in the breast cancer patient.